Severe anaemia secondary to a perforated gastric ulcer in a male alpaca - Matthias Gerhard Wagener; Teresa Maria Punsmann; Sven Kleinschmidt; Ralf Surholt; Saskia Neubert; Hannah Marahrens; Thekla Großmann; Martin Ganter (Irish Veterinary Journal, 2023)
Abstract Background Anaemia is a common condition in alpacas and attributable to a variety of causes. Severe anaemia with a packed cell volume (PCV) less than 10% is frequently diagnosed, usually due to blood loss resulting from haemonchosis. Many South American camelids (SACs) also suffer from gastric ulcers, which are often associated with anaemia in other species. However, in alpacas and llamas, gastric ulcers usually do not lead to anaemia due to blood loss according to the current literature. There are no detailed clinical and laboratory data on this condition in the scientific literature so far. Case presentation We report on the case of a nine-year-old male alpaca that was presented to the clinic with suspected forestomach acidosis. The animal showed clinical signs of colic, hypothermia, tachypnea, tachycardia, pale mucous membranes, and died shortly after admission to the clinic. Laboratory diagnosis revealed a markedly decreased haematocrit (0.13 l/l), leucopaenia with band neutrophils, azotaemia, hypocalcaemia, hyperphosphataemia and vitamin D deficiency. Post-mortem examination revealed multiple ulcers in the first and third compartment with perforation of one ulcer in the first compartment, resulting in intraluminal blood loss and purulent peritonitis. Conclusions To the authors’ knowledge, this is the first detailed description of clinical and laboratory data of severe anaemia due to a perforated gastric ulcer in a SAC. Although the current literature suggests that severe blood loss due to gastric ulcers does not occur in SACs, this condition should be considered as a possible differential diagnosis in anaemic animals. Clinical indicators can be colic and pale mucous membranes.